(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
The studies were carried out to establish more precise parameters for citronella (C. winterianus Jowiti) post-harvest, and to optimize drying time and essential oil quantitative/qualitative yield. Five treatments were designed (30ºC, 40ºC, 50ºC, 60ºC and 70ºC), with 14 repetitions of the drying process and 12 of the essential oil extraction. Drying at 60ºC gave the best results for drying time (48 hours until weight stabilization), and also for extracted oil quantity (1.228 ± 0.127% over dry weight). Essential oil content showed high quantitative variations. The main compound found was neral, except in the 50ºC treatment, where citronelal was the main compound.